TRANSFORMASI DIGITAL RUMAH SAKIT MELALUI MEDICAL ARTIFICIAL INTELLIGENCY, HEALTHCARE SERVICE QUALITY, DAN PERCEIVED USEFULNESS: DAMPAKNYA TERHADAP PATIENT SATISFACTION DI RSUP DR. SITANALA - Hasan, Afrizal; Hasanah, Neneng; Anggiani, Sarfilianty (INSTITUT TEKNOLOGI DAN BISNIS INDOBARU NASIONAL, 2025)
Digital transformation in the healthcare sector is a strategic effort to improve efficiency, service quality, and patient satisfaction. The application of intelligent technology such as medical artificial intelligence, accompanied by improving the healthcare service quality and perceived usefulness of technology, is an important element in creating a superior service experience. This study aims to analyze “ Transformation of Hospital Through Medical Artificial Intelligency, Healthcare Service Quality, and Perceived Usefulness: Its Impact on Patient Satisfaction at RSUP Dr. Sitanala, Tangerang. A total of 234 respondents from inpatients in various healthcare units at RSUP. Dr. Sitanala, Tangerang have been collected from questionnaires directly and through the google forms application. Sampling in this study used purposive sampling. Data analysis used SmartPLS 3.0 as software. The findings of this study indicate that medical artificial intelligence, healthcare service quality, and perceived usefulness have a positive and significant effect on patient satisfaction.